2019
DOI: 10.5114/cipp.2019.92957
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dimensions of grandiose narcissism and Facebook addiction among university students

Abstract: backgroundThe present study aimed to examine the relationship between different dimensions of grandiose narcissism and Facebook addiction among undergraduate students. In the Polish population, grandiose narcissism has been shown to have a four-factor structure: Self-sufficiency, Vanity, Leadership and Admiration demand. Studies consistently show that grandiose narcissism is related to Facebook addiction. However, it is still not clear which dimensions of grandiose narcissism are particularly related to this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Our results revealed that admiration, sociability, and negative social potency are positively associated with problematic Snapchat use, and only negative social potency is positively associated with problematic Facebook use. Our finding that admiration and sociability are only related to problematic Snapchat use and not problematic Facebook use is surprising considering problematic Facebook use has previously been related to one’s need for admiration ( Balcerowska et al, 2019 , Casale and Fioravanti, 2018 ). This discrepancy could, for example, be due to assessment differences (both of these prior studies used a different measure of admiration) or cultural differences (both of these prior studies were conducted in Europe, while the current study was conducted in the U.S.).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our results revealed that admiration, sociability, and negative social potency are positively associated with problematic Snapchat use, and only negative social potency is positively associated with problematic Facebook use. Our finding that admiration and sociability are only related to problematic Snapchat use and not problematic Facebook use is surprising considering problematic Facebook use has previously been related to one’s need for admiration ( Balcerowska et al, 2019 , Casale and Fioravanti, 2018 ). This discrepancy could, for example, be due to assessment differences (both of these prior studies used a different measure of admiration) or cultural differences (both of these prior studies were conducted in Europe, while the current study was conducted in the U.S.).…”
Section: Discussionmentioning
confidence: 53%
“…Importantly, researchers have previously investigated the relationship between problematic SNS use and certain aspects of social reward that could drive this use. For example, studies have revealed a positive relationship between problematic SNS use and one’s need to belong and one’s need for admiration ( Balcerowska et al, 2019 , Casale and Fioravanti, 2018 , Ho et al, 2017 ). However, no study has yet compared problematic use between Snapchat and Facebook, or examined differences in trait social reward preferences which would motivate disparate use of these SNSs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that a specific dimension of grandiose narcissism (i.e., passive and dependent on others) is a risk factor for PSNSU, whilst the active and independent dimension could function as a protective factor [84], therefore not all aspects of the trait might contribute to addictive behaviour. Furthermore, a recent review study found that the association between vulnerable narcissism and PSNSU is under-researched [85].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 13 studies used the Bergen Facebook Addiction Scale (BFAS; Andreassen et al, 2012) with different ranges (1 -5; 6 -30; 18 -90). Out of the 6 studies using the 6-30 range, the means went from 8.98 (SD = 3.64) (Brailovskaia et al, 2018) to 12.88 (4.93) (Balcerowska et al, 2019). The study by Siah et al (2021) used the Bergen Social Networking Addiction Scale (Andreassen et al, 2012) and four studies used its most up-to-date version, the Bergen Social Media Addiction Scale (BSMAS; Andreassen et al, 2016).…”
Section: Description Of Studiesmentioning
confidence: 99%